Synergistic Effect of Amino Acids and NPK on Growth Dynamics, Yield Components, and Grain Productivity of Inpari 32 Rice Variety (Oryza sativa L) - Tita Kartika Dewi; Wirja; Chalvyn Silasa Pakidi; Ida Marina; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2026)
Rice productivity improvement is essential to support food security and sustainable agricultural development. This study aimed to evaluate the synergistic effects of amino acids and NPK fertilizer on growth dynamics, yield components, and grain productivity of the Inpari 32 rice variety (Oryza sativa L.). The experiment was conducted in Sukatani Village, Subang Regency, Indonesia, from July to October 2025 using a Randomized Block Design with nine treatment combinations consisting of three amino acid concentrations (5, 10, and 15 mL L⁻¹) and three NPK fertilizer doses (50, 100, and 150 kg ha⁻¹), replicated three times. Observed parameters included plant height, tiller number, leaf area index, productive tillers, panicle number, filled grains per panicle, 1000-grain weight, harvest dry grain yield, and milled dry grain yield. The results showed that the combination of 10 mL L⁻¹ amino acids and 100 kg ha⁻¹ NPK fertilizer produced the highest plant height (74.42 cm), tiller number (26.20 tillers), productive tillers (19.37), filled grains per panicle (126.57 grains), 1000-grain weight (26.50 g), and milled dry grain yield (7.93 kg plot⁻¹). The synergistic interaction between amino acids and NPK improved nutrient uptake efficiency and physiological performance, resulting in higher grain productivity. Therefore, the combined application of amino acids and NPK fertilizer can be recommended as an effective strategy for sustainable rice production.